PENGARUH RETURN ON EQUITY (ROE) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PT WIJAYA KARYA (PERSERO) TBK PERIODE 2013 - 2022 - Laurent, Vincentius; Surahman, Arif (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of Return on equity  and Earning Per Share on Share Price at PT Wijaya Karya (Persero) Tbk. The method used is quantitative method. The sampling technique used is saturated sampling in the form of financial statements of PT Wijaya Karya (Persero) Tbk for 10 years in the period 2013-2022. Data analysis using classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of this study are Return on equity  has no significant effect on Stock Price with hypothesis testing obtained t value < t table or (1.610 < 2.306). Earning Per Share has no significant effect on Stock Price with the obtained t value < t table or (-0.065 < 2.306). This is also reinforced by the value of ρ value < Sig.0.05 or (0.950 > 0.050). Return on equity  and Earning Per Share can be obtained regression equation Y = 1275.241 + 66.394X1 - 0.231X2.  Thus there is a significant effect of Return on equity  and Earning Per Share on Stock Price.